Distribution patterns of Baetis (Ephemeroptera: Baetidae) as tolerant taxa in freshwater biological monitoring - Suhaila A.H.,; Siti Hamidah I.,; Nur Aida H., (Penerbit Universiti Kebangsaan Malaysia, 2017)
The abundance and distribution of seven Baetis sp. (Baetis gombaki, Baetis idei, Baetis illiesi, Baetis laetificus, Baetis lepidus, Baetis minutus and Baetis mirabilis) from Order Ephemeroptera (Family: Baetidae) in four rivers from Bukit Merah catchment area, Perak were studied. From this study, Sungai Ara was classified as the most preferred habitat and hotspot area for all the Baetis sp. Out of seven species, B. illiesi (120 individuals) was the dominant species while B. laetificus was the most sensitive taxa. This study indicates that abundance, distribution and composition of Baetis sp. in each river appeared to respond to the water quality parameters. B. idei showed positive correlation with water temperature (r=0.723, P=0.00) and Biochemical Oxygen Demand (r=0.719, P=0.00). B. gombaki was the least sensitive species as it is only correlated with water temperature (r=0.499, P=0.001). Sungai Kurau was considered as the less preferred habitat for Baetis. Copper (Cu) was positively correlated with the abundance of B. idei, B. lepidus and B. minutus (P<0.05) at a tolerable concentration (mean 0.64±0.4 ppm). It can be concluded that chemical parameters of the rivers do affect the abundance and diversity of Baetis species.